The Utilization of Quality Antenatal Care in Pakistan: Analyzing Health Inequity in Various Periods - Naz, Lubna (Journal of Population and Social Studies [JPSS], 2019)
This paper consists of two research questions, both which address socioeconomic inequalities of antenatal care in Pakistan. The first is a query probing whether, definitively, there is non-utilization of quality antenatal care, also referred to as skilled birth attendants. And the second is that, if there is such, what the specific factors are that bring about this inequality. To assess this, the Pakistan Demographic and Health Surveys of 1990-91, 2006-07 and 2012-13 were used to establish both absolute and relative measures of inequality. The results show that the rate ratio, a relative measure of quality antenatal care, increased from 2.3 in 1990-91 to 6 in 2006-07, and reached a higher value of 9.1 in 2012-13. In contrast, the range difference, the absolute measure, decreased throughout the sequence of the survey periods. While the Lorenz curves indicated a concentration of non-utilization of quality antenatal care amongst the poorest in the years studied in the surveys, the Slope index of inequality showed a decrease by 39% when women moved from the lowest to the highest socioeconomic status. Among the sources of inequality, the socioeconomic status contributed the largest percentage, which was 44%, followed by place of residence, at 21%, a husband’s education at 14%, and the woman’s age at 13%. Thus, the measure of inequality plays a vital role in determining the size and direction of inequity in quality antenatal care when examined in the context of multiple survey periods.